2017
DOI: 10.1002/clc.22715
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation dysregulations in valvular atrial fibrillation

Abstract: Background The epigenetic changes underlying the development of atrial fibrillation (AF) remain incompletely understood. Limited evidence suggests that abnormal DNA methylation might be involved in the pathogenesis of AF. In the present study, we evaluated the methylation status of genomic DNA from myocardial tissue in AF patients and sinus rhythm (SR) patients systematically. Hypothesis DNA methylation dysregulations will be associated with valvular AF. Methods Right atrial myocardial tissue was obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…DNA methylation is a pre-transcriptional modification, which is able to change transcriptional process, by the addition of methyl groups to specific nucleotides of the DNA. This procedure causes inactive gene expression due to the fact that the methyl binding protein prevents the transcriptional factor from binding to DNA and thus it proceed to the next step [ 200 , 201 , 202 ]. It is commonly believed that hypomethylation in diseases is more frequent than hypermethylation [ 203 ].…”
Section: Epigenetics Of Atrial Fibrillationmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation is a pre-transcriptional modification, which is able to change transcriptional process, by the addition of methyl groups to specific nucleotides of the DNA. This procedure causes inactive gene expression due to the fact that the methyl binding protein prevents the transcriptional factor from binding to DNA and thus it proceed to the next step [ 200 , 201 , 202 ]. It is commonly believed that hypomethylation in diseases is more frequent than hypermethylation [ 203 ].…”
Section: Epigenetics Of Atrial Fibrillationmentioning
confidence: 99%
“…However, in AF context, global DNA methylation levels are significantly increased in AF patients, having a positive correlation with age [ 202 ]. Furthermore, it has been demonstrated that DNA methylation plays an important role in the maintenance of cardiac fibrosis, where DNA methyltransferases 3A ( DNMT3A ) likely plays an essential role in Ras association domain family member 1A ( RASSF1A ) mediated up-regulation of ERK1/2 [ 204 , 205 ].…”
Section: Epigenetics Of Atrial Fibrillationmentioning
confidence: 99%
“…DNA methylation occurs at the global and specific gene promoter level. Abnormal DNA methylation can affect the transcription and expression of key regulatory genes [ 6 ]. For example, the overall DNA methylation level of the AF group was significantly higher compared to controls [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal DNA methylation can affect the transcription and expression of key regulatory genes [ 6 ]. For example, the overall DNA methylation level of the AF group was significantly higher compared to controls [ 6 ]. Genome mutations are composed of single-nucleotide variants (SNVs), small insertions-deletions (indels), copy number alterations, and translocations [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation, a pre-transcriptional modification characterized by the addition of methyl groups to specific nucleotides, regulates the stability of gene expression states and maintains genome integrity by collaborating with proteins that modify nucleosomes (Ma et al, 2014;Tao et al, 2016;Shen et al, 2017). Previous studies considered that changes in DNA methylation states contribute to the regulation of biological processes underlying AF, such as fibrosis, atrial dilatation, atrial fibroblast proliferation and differentiation from fibroblasts into myofibroblasts (Zhao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%